No Taxation without Administration: Bringing the State Back into the Public Finance of Developing Countries - Jensen, Anders D.; Weigel, Jonathan L. (Journal of Economic Literature, 2026)
The empirical economics literature on taxation in developing countries has centered on the importance of third-party information for enforcement. Yet, while surely a long-run objective, leveraging such information remains out of reach in many developing countries due to largely informal economies and low state capacity. This article examines an emerging complementary literature focused on strengthening the “sinews” of state capacity: tax administration. We argue that reforms to the organizational structure, personnel management, and task management of tax authorities have potential to raise tax capacity in developing countries. We also argue that efforts to improve the state’s legitimacy—popular acceptance of its right to tax—can increase capacity and may complement investments in tax administration. Our approach bridges a long-standing divide between how scholars in public finance and political economy approach tax capacity building in developing countries. (JEL D63, D73, H20, H50, K34, M50, O17)